Decoding Neurogenetic Profiling And Corporate Panchayat Governance: Legal And Psychological Framework For Mncs In Chennai" (The Review of Diabetic Studies, 2025)
The determination towards the internal indicators of emotions are sensation, perception, attitude, decision making capabilities are analysed within the basic concept of psychology and different aspects of neuro psychology, psychogenetics and neuro cognition. The negative integration of emotions is always analysed with basic systems involved in criminal and forensic psychology, the application of each genera of psychology are directly or indirectly related with the Cognitive psychology which employs a diverse array of techniques to investigate human understanding, diagnosis, problem-solving, and memory through clinical psychology. From the literature we could infer that there are no attention given to corporate disputes or conflicts in more informal way and the need for addressing those disputes do need corporate law panchayats that could enhance the implementation of concerns of disputes and conflicts caused in the corporate settings. The overarching objectives include collecting and analysing data, developing and testing theories, and applying these findings in various settings. With neurogenetic and  Cognitive psychology is the scientific study of mental processes, encompassing how individuals perceive, remember, think, reason, and solve problems. It seeks to explain the mechanisms behind human thought, emotion, creativity, language, and problem-solving, providing a deeper understanding of why people think in ways. The term "cognition" itself is derived from the Latin word "Cognos Cere," meaning "to know" or "to come to know," and it broadly includes all processes involved in acquiring, storing, retrieving, and processing knowledge, such as noticing, focusing, recalling, classifying, and making decisions. In this study the role of perception, attention and decision-making skills of human has been analysed and derived to supplement the identification of stress factors in the employees in organisational settings.to address the drawbacks of conflict management in the aspects of stress, trauma and other psychological distress which are temporary related with work and epigenomics that could cause predispositions of stress with increase in health risks directly or indirectly.In this research the each and every indicators are analysed and explained from its origin in psychological way to enhance the importance of cognitive, behavioural, criminal, forensic, and other aspect of psychology to overcome the psych legal drawback in HR policies in the corporate settings.